Mapa semântico na alfabetização e letramento: reflexões sobre o uso do recurso pedagógico no ensino e aprendizagem de surdos em Manaus/AM - Rentes, Mircéa de Souza (Brasil, 2024)
This paper investigates the use of conceptual and semantic maps as teaching resources for deaf students, based on a bilingual approach. The research emerged from the experiences in the course "Didactic-Pedagogical Materials for Teaching Libras as L1" and in the PACE II project: Bilingual Skills for Deaf Students: Letrônico Method, both linked to the Libras Language course at UFAM. The specific objectives include: investigating whether and how teachers use these maps in their classes, verifying the application of these tools in the literacy and literacy process of deaf students, and comparing the adequacy of the methodologies employed. The methodology used was qualitative, involving interviews with teachers from public schools in Manaus and bilingual education to analyze and understand the use of conceptual and semantic maps in the classroom. The results indicate that, although they recognize the value of conceptual and semantic maps, their effective implementation depends on the adequacy of the materials according to the needs of the students. Adapting these tools for deaf students has proven effective in developing reading and writing comprehension. It is concluded that conceptual and semantic maps are promising tools for bilingual teaching of deaf students, as long as they are used flexibly and with adequate support. It is recommended that teachers continue to be trained and that new strategies for integrating these resources into the curriculum be researched.